The COVID-19 pandemic and positive reflections on Ramadhan - Mohd Zaini, Ahmad Faidhi; Abdul Rashid, Aneesa (International Journal of Human and Health Sciences (IJHHS), 2021)
This year the Ramadhan holy month of the Muslim calendar fell amidst a pandemic. Ramadhan is a month of worship, where many of the normal practices involve among other things; social gathering. Due to the COVID-19 pandemic, many practices could not be done. This article looks into the positive reflections of Ramadhan during a pandemic.